ChemInform Abstract: Amine α‐Heteroarylation via Photoredox Catalysis: A Homolytic Aromatic Substitution Pathway. Issue 12 (March 2015) - Prier, Christopher K.; MacMillan, David W. C.
Abstract Five‐ (II) and six‐membered heteroarenes (IV) are viable coupling partners for the title reaction with cyclic and acyclic amines [(I) and (VI)].